Acinetobacter baumannii OxPhos inhibitors as selective anti-infective agents. Issue 2 (15th January 2015) - Rubin, Harvey; Selwood, Trevor; Yano, Takahiro; Weaver, Damian G.; Loughran, H. Marie; Costanzo, Michael J.; Scott, Richard W.; Wrobel, Jay E.; Freeman, Katie B.; Reitz, Allen B.
Graphical abstract